Using case study within a sequential explanatory design to evaluate the impact of specialist and advanced practice roles on clinical outcomes: The SCAPE Study - Elliott, Naomi; Comiskey, Catherine; Begley, Cecily; Higgins, Agnes; Coyne, Imelda; Lalor, Joan (My University, 2013)
Background: The role of the clinical nurse/midwife specialist and advanced nurse/midwife practitioner is complex not least because of the diversity in how the roles are operationalised across health settings and within multidisciplinary teams.This aim of this paper is to use The SCAPE Study: Specialist Clinical and Advanced Practitioner Evaluation in Ireland to illustrate how case study was used to strengthen a Sequential Explanatory Design. Methods. In Phase 1, clinicians identified indicators of specialist and advanced practice which were then used to guide the instrumental case study design which formed the second phase of the larger study. Phase 2 used matched case studies to evaluate the effectiveness of specialist and advanced practitioners on clinical outcomes for service users. Data were collected through observation, documentary analysis, and interviews. Observations were made of 23 Clinical Specialists or Advanced Practitioners, and 23 matched clinicians in similar matched non-postholding sites, while they delivered care. Forty-one service users, 41 clinicians, and 23 Directors of Nursing or Midwifery were interviewed, and 279 service users completed a survey based on the components of CS and AP practice identified in Phase 1. A coding framework, and the generation of cross tabulation matrices in NVivo, was used to make explicit how the outcome measures were confirmed and validated from multiple sources. This strengthened the potential to examine single cases that seemed 'different', and allowed for cases to be redefined. Phase 3 involved interviews with policy-makers to set the findings in context. Results: Case study is a powerful research strategy to use within sequential explanatory mixed method designs, and adds completeness to the exploration of complex issues in clinical practice. The design is flexible, allowing the use of multiple data collection methods from both qualitative and quantitative paradigms. Conclusions: Multiple approaches to data collection are needed to evaluate the impact of complex roles and interventions in health care outcomes and service delivery. Case study design is an appropriate methodology to use when study outcomes relate to clinical practice.
PUBLISHED
https://doi.org/10.1186/1471-2288-13-55
Keywords: Advanced practice; Case study; Complex evaluation; Midwifery; Nursing; Specialist practice; Workforce; Advanced practice; Case study; Complex evaluation; Midwifery; Nursing; Specialist practice; Workforce; Digital Engagement